Assessing Genetic Variation in Resistance to Pinewood Nematode (Bursaphelenchus xylophilus) in Pinus radiata D. Don Half-Sib Families - María Menéndez-Gutiérrez (MDPI AG, 2021)
Full understanding and control of pine wilt disease (PWD) is a work in progress and breeding for disease resistance constitutes an essential management strategy for reducing its impact, as evidenced by advanced breeding programs in countries such as Japan. Since Pinus radiata is one of the most commercially relevant species in northern Spain, we designed a study to assess genetic variation in susceptibility to this pathogen using 44 P. radiata half-sib families from the Galician breeding program. Three Bursaphelenchus xylophilus (pinewood nematode, PWN) inoculation experiments were performed to evaluate disease-related variables, estimate genetic parameters, and study sources of genotype by environment interaction (G × E). We also looked at differences in the constitutive chemical compounds of susceptible and non-susceptible individuals. The results showed great variation in PWN susceptibility, with survival rates for P. radiata families ranging from 0% to 90%. In addition, heritability estimates (hi2 = 0.43, hf2 = 0.72) and genetic gain (>26% selecting 50% of the families) were both moderately high for survival. Significant differences in several constitutive chemical compounds were found between susceptible and non-susceptible seedlings in the two susceptibility groups considered. These results confirm the potential of breeding to obtain P. radiata genotypes that are resistant to pine wilt disease and open possibilities for mitigating its future impact on P. radiata stands.